Spectrophotometric Determination of Ceftibuten in Bulk and in Pharmaceutical Formulations - R. Vijayalakshmi; P. Bhargavi; P. Srujana Kumari; P. Sruthi; M. D. Dhanaraju (E-Journal of Chemistry)
A simple and cost effective spectrophotometric method is described for the determination of ceftibuten in pure form and in pharmaceutical formulations. The method is based on the formation of blue colored chromogen, when the drug reacts with Folin-Ciocalteu (F-C) reagent in alkaline medium. The colored species has an absorption maximum at 798 nm and obeys Beer’s law in the concentration range 10-50 mcg/mL. The apparent molar absorptivity and sandell’s sensitivity were 0.4583x104 and 0.3x104 respectively. The slope and intercept of the equation of the regression line are 4.5x10-3 and 1.3x10-5 respectively. The optimum experimental parameters for the reaction have been studied and the validity of the described procedure was assessed. Statistical analysis of the results has been carried out revealing high accuracy and good precision. The proposed method was successfully applied for the determination of ceftibuten in pharmaceutical formulations.